Demographic influences on word associations - Aleknavičiūtė, Marta Marija (Taikomoji kalbotyra, 2025)
Word associations are verbal responses to cues, typically studied using word association tests. This study examines how demographic factors, such as gender, age, settlement size, ethnographic region and education level, influence word associations. Data were collected online using a 30-stimulus research tool, resulting in 11,046 responses from 389 participants. Stereotypy, defined as the tendency for the same response to recur for a given cue word, was analyzed using multiple regression. The findings indicate that the associations provided by younger participants were more stereotypical than those of older participants, and women’s responses exhibited a higher degree of stereotypy compared to men’s. However, other demographic factors did not show a significant impact. The findings suggest that demographic factors help shape word associations, contributing to the growing body of research that highlights the influence of various factors on associative patterns. Additionally, this study provides valuable insights into Lithuanian, an under-researched language in the field of word association studies.